Changing the Religiosity of Indonesian Muslims in the New Normal Era - Halim, Abdul; Hosen, Nadirsyah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
This study examined new religious patterns and behaviours in Indonesian Muslims during the New Normal era. This new religiosity is an impact of government regulations and recommendations from community organisations regarding social and physical distancing restrictions due to the spread of Covid-19. This study used a sociological approach to analyse changes in religious and social behaviour of Indonesian Muslims in public spaces qualitatively. This study found five main aspects that indicate a new form of religiosity for Indonesian Muslims in the New Normal era, namely; a shift in worship practices from a public space to a private space, a decrease in the capacity of the physical space that has an impact on decreasing the routine of worship, the emergence of new challenges for the authorities and public policy to prepare an area for more personal religious activities, the disappearance of symbolic worship practices, and finally, the blurring of abangan Muslim groups based on waqi'iyah (contemporary/contextual) ijtihad. These findings are analysed using the theory of public space from Jurgen Habermas's. This study proposes a new pattern of religiosity for Indonesian Muslims in the New Normal era, i.e., the adjustment of Shari'a by way of independent legal reasoning to maintain a wider maslahat, public welfare.